A remark on semistability of quiver bundles - Schmitt, Alexander (Eurasian Mathematical Journal, 2012)
In this paper, we introduce a new semistability condition for quiver bundles which generalizes both the notion found by Álvarez-Cónsul and by the author. We construct moduli spaces for the semistable bundles, applying Geometric Invariant Theory.